Masailul Al-Fiqhiyyah Kontemporer dan Implikasinya terhadap Pembentukan Moral Peserta Didik - Mira Salpina; Riska Khodijah; Desmi Satriana (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Contemporary developments in science, technology, and socio-cultural dynamics have given rise to various new fiqh issues (masailul al-fiqhiyyah al-mu‘ashirah) that were not explicitly discussed in classical Islamic jurisprudence. These contemporary fiqh issues demand contextual ijtihad that is responsive to current realities while remaining grounded in Islamic legal principles. This study aims to analyze contemporary fiqh issues and examine their implications for the moral formation of students in Islamic education. This research employs a qualitative library research approach by analyzing classical fiqh literature, contemporary fiqh studies, and relevant educational theories. The findings indicate that contemporary fiqh issues such as digital ethics, biomedical technology, and socio-economic practices carry significant moral dimensions that directly influence students’ attitudes and behavior. Integrating contemporary fiqh discourse into Islamic education encourages critical thinking, moral reasoning, and ethical awareness among learners. Therefore, contemporary fiqh learning not only functions as a legal reference but also as a strategic instrument for strengthening students’ moral character in accordance with Islamic values. The study implies that Islamic education institutions should contextualize fiqh instruction to address contemporary moral challenges faced by students.